Ways to improve the confinement of fast ions in stellarators by RF waves: general analysis and application to Wendelstein 7-X. (12th April 2017) - Kolesnichenko, Ya.I.; Lutsenko, V.V.; Rudenko, T.S.; Helander, P.
Abstract: A possibility to improve the confinement of energetic ions in stellarators by transforming trapped particles into passing ones using RF waves is investigated. It is concluded that waves with frequencies around the ion gyrofrequency or lower can, in principle, be used for this purpose if certain requirements are satisfied. The suitability of the W7-X ICRH system is considered, and other means for achieving fast-ion confinement are discussed.